Quantum Effects without Quantum Fields: Feynman's Amplitudes in Classical Electrodynamics - Nieto-Chaupis, Huber (2020)
We derived their classical counterpart of Feynman's amplitudes for electron and photons interaction in the super-intense regime through the Hartemann-Kerman theory in conjunction to the Reiss-Eberly criterion of quantization. Our derivation is supported by the conjecture of Ritus-Nikishov by which field quantization might have its origin through artificial mechanism. In this manner, the classical counterpart might also provide an alternative path to arrive to pure Quantum Mechanics processes. Thus, in this paper we demonstrate that nonlinear Compton and the corresponding “pseudo” Feynman rules can also de extracted from a pure classical description. We present various spectra for simple and double Compton scattering that are in fully agreement with the existent Literature.